Elements of statistical reasoning - Minium, Edward W. 1917- (John Wiley & Sons, 1999)
This text stresses conceptual development and the logic of statistics for use in the Behavioral Sciences. It is designed for those who need to evaluate statistical findings. Coverage includes estimation procedures, independent samples t-test, Steven's scales of measurements, Pearson correlation coefficient. Updated to include Turkey's HSD test on factorial analysis of variance and Spearman's rho on assumption-free tests and all chapter have been edited to enhance clarity and flow, to simplify numbers in the worked problems, and to align all examples with the behavioral sciences.